A novel zoonotic genotype related to Echinococcus granulosus sensu stricto from southern Ethiopia. Issue 10 (September 2016) - Wassermann, Marion; Woldeyes, Daniel; Gerbi, Banchwosen Mechal; Ebi, Dennis; Zeyhle, Eberhard; Mackenstedt, Ute; Petros, Beyene; Tilahun, Getachew; Kern, Peter; Romig, Thomas
Graphical abstract: Highlights: The present study describes a novel genetic variant of Echinococcus granulosus sensu stricto. Phylogenetic analyses have been carried out using the complete mitochondrial (mt) genome. In addition to the mt genome the distance values of two nuclear genes were analysed. This Echinococcus specimen is clearly distinct from haplotypes of the G1–G3 cluster. The new genotype Gomo is pathogenic to humans. Abstract: Complete mitochondrial and two nuclear gene sequences of a novel genotype (GOmo ) related to Echinococcus granulosus sensu stricto are described from a metacestode isolate retrieved from a human patient in southwestern Ethiopia. Phylogenetically, the genotype is positioned within the E. granulosus sensu stricto/ Echinococcus felidis cluster, but cannot easily be allocated to either species. Based on different mitochondrial DNA markers, it is closest to the haplotype cluster that currently defines the species E. granulosus sensu stricto (which includes variants showing the widely cited G1, G2 and G3 sequences), but is clearly not part of this cluster. Pairwise distances between GOmo and E. granulosus sensu stricto are in the range of those between the most distant members of the Echinococcus canadensis complex (G6–10) that were recently proposed as separate species. At this stage, we prefer to list GOmo informally as a genotype rather than giving it any taxonomic rank because our knowledge rests on a single isolate from a dead-end host (human), and its lifecycle is unknown. According to data on molecularly characterised Echinococcus isolates from this region, GOmo has never been found in the usual livestock species that carry cystic echinococcosis and the possibility of a wildlife source of this newly recognised zoonotic agent cannot be excluded. The discovery of GOmo adds complexity to the already diverse array of cystic echinococcosis agents in sub-Saharan Africa and challenges hypotheses on the biogeographical origin of the E. granulosus sensu stricto clade.